ANALISIS PENGARUH ADVERTISING DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN - Aini, Nike Nur; Mulyati, Awin; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2018)
In this study the authors conducted research on the influence of Advertising and Personal Selling on Purchase Decision. The method used is multiple linear regression. The population in this study are consumers who use Wardah cosmetic products. The number of samples used in this study as many as 100 respondents taken from consumer cosmetics Wardah in Transmart Rungkut accidental sampling.The results showed that Advertising has a positive and significant effect on purchasing decisions partially accepted. Personal Selling has a positive and significant impact on purchasing decisions. Advertising and Personal Selling together positively and positively influence Wardah's cosmetic purchase decision. The most dominating factor in purchasing decisions is Advertising.Keywords: Advertising, personal selling, and purchasing decisions